ANTIBACTERIAL ACTIVITY IN EARTHWORM COELOMIC FLUID LAMPITO MAURITII - M.P, Deepthi; P, Kathireswari (Kongunadu Research Journal, 2016)
Earthworms are the first annulated coelomate organism with haemoglobin in the plasma as carrier of oxygen and carbon dioxide. They have the antimicrobial activity against the disease causing micro organisms. In the present study antibacterial activity of earthworm coelomic fluid Lampito mauritii were confined against disease causing micro organisms through the inhibition zone formation by well diffusion method as well as disc diffusion method.